2021
DOI: 10.5815/ijcnis.2021.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Methods of Evaluation of Efficiency of Distance Learning System Functioning

Abstract: The current pace of development of information technology has created the preconditions for the emergence of a wide range of tools for providing educational services using distance learning technologies. This is confirmed by the intensification of the use of distance learning systems in the conditions of sanitary and epidemiological restrictions and the need for acute cost savings. The existing scientific and methodological apparatus for studying the quality of functioning of distance learning systems is most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The new appreciation, which was born after it, is rooted in the soil of traditional and modern technology museums and is a new form of museum under the new network environment, so it is different from the concept pursuit and practice of traditional museums. Therefore, in the implementation of digital art museums, the paper puts forward the following suggestions to promote the construction of a digital museum [19,20].…”
Section: Methods Of Computer Network Security Protectionmentioning
confidence: 99%
“…The new appreciation, which was born after it, is rooted in the soil of traditional and modern technology museums and is a new form of museum under the new network environment, so it is different from the concept pursuit and practice of traditional museums. Therefore, in the implementation of digital art museums, the paper puts forward the following suggestions to promote the construction of a digital museum [19,20].…”
Section: Methods Of Computer Network Security Protectionmentioning
confidence: 99%
“…If a hardware failure occurs, the self-recovery is to find the workstations to which the software components are redistributed with the establishment of new network connections. As at the system level, it is necessary to periodically check the condition of various components of the equipment and act accordingly [7,16,29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Particular attention to these issues exists in researchers of the properties of functional stability of complex technical systems that are able to self-organize under the influence of destabilizing factors [8,9,28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The gained results have shown that the optimal learning effect is achieved in the time proportion 2:1 of traditional face-to-face teaching and digital learning. O. Barabash, A. Musienko, and others [18] suggest a complex approach to assessing the effectiveness of the distance learning process, based on the methods of probability theory and hierarchy analysis. They were encouraged to start the research by the fact that scientists usually assess the effectiveness of single elements of the distance learning system and appropriate quality indicators.…”
Section: Disscussionmentioning
confidence: 99%